Protection for the banks of the Moche river: sustainable structure - Alva Rodriguez, Fabian Alberto (2024)
This research aims to make a proposal for a sustainable structure for the protection of the Moche River in Trujillo, La Libertad. The methodology used focused on quantifying the biological, topographic, hydrological, hydraulic, structural and environmental variables. According to the eco-friendliest theories used in international literature, as well as technical standards E030, water resources law and the environmental impact law. ArcGIS pro HEC-RAS and Gawac 3.0 mathematical models were used to analyze and process the variables; and SPSS29 statistics. The main results were that favorable conditions exist to execute the sustainable structure. The maximum flood 643.47 m3/s for a return period of 140 years and a maximum water depth of 7.62. The dimensions of the gabion structure ranged between 4 and 8 meters in accordance with the topography of the river bank. The gabion wall had 58% direct and indirect negative impacts, while 78% were positive impacts to the environment. It is concluded that gabions are a sustainable structure for the care and protection of the environment and society.